Environmental effect of lubricity additives through dielectric molecular parameters. (2020) - Prathima, A.; Karthikeyan, S.; Radhi Devi, K.; Usha, K.; Shanthi, M.
Abstract: Lubricant additives are chemicals, nearly always-organic or organometallic, that are added to oils in quantities of a few weight percent to improve the lubricating capacity and durability of the oil. Specific purposes of lubricant additives are improving the wear and friction characteristics by provision for adsorption and extreme pressure lubrication, improving the oxidation resistance, control of corrosion, control of contamination by reaction products, wear a and other debris, reducing excessive decrease of lubricant viscosity at high temperatures, enhancing lubricant characteristics by reducing the pour point and inhibiting the generation of foam. These properties depend upon the molecular interactions between the chemical additives. So that, this study target on investigating the molecular interactions through the dielectric parameters such as Kirkwood correlation factor, Excess permittivity, Bruggemann factor and Dipolar excess free energy in the lubricative binary mixtures, 1) caprylic acid + 2-ethyl-1-hexanol and 2) valeric acid + 2-ethyl-1-hexanol. The above dielectric parameters have been calculated from the experimentally measured values of capacitance and refractive index of mixtures, at temperatures 303 K, 313 K and 323 K. In the above studied systems, existence of short and long range, homo and hetero interactions are identified. These interactions are found to be concentration and temperature dependent. The hetero interaction results in the formation linear as well as closed multimers in the mixture. Due to the existing interactions, structural changes are found to take place.